La crisis económica y la deserción escolar - Cunduri Muñoz, Brayan Alexander (2026)
The primary objective of this research was to identify the impact of various factors on school dropout rates at the Manuel del Pino Intercultural Bilingual Educational Center in the Chismaute Yurac Rumi community. To this end, an appropriate methodology was used to analyze the data obtained. This mixed-methods (quantitative and qualitative) research design is non-experimental and descriptive. The data was collected through a survey consisting of 10 questions covering the two study variables, administered to students and their parents, and through an interview consisting of 8 questions administered to the teachers at the Educational Center. The study concludes that the economic crisis not only affects access to educational resources but also drives parental migration, family fragmentation, and emotional stress mong students, thereby reducing their performance and motivation to remain in the educational system. Likewise, a lack of institutional support and insufficient support programs or subsidies to mitigate the crisis's effects on education were identified. School dropout results from a combination of economic, social, and cultural factors, with the economic crisis serving as a trigger for migration and child labor, two of the most significant causes. Furthermore, Intercultural Bilingual Education represents a fundamental pillar of students' cultural identity, but it requires strengthened institutional support programs to guarantee its effectiveness in crisis contexts. The implementation of financial support programs, improved communication between schools and the community, and the development of pedagogical strategies adapted to students' socioeconomic conditions are recommended. These measures would help reduce school dropout rates and ensure the retention of children and young people in the education system, promoting equity and access to quality education.